Chemical signals in vertebrates 12 - Dehnhard, Martin; East, Marion L. (Springer New York, 2013)
This volume presents the proceedings of "Chemical Signals in Vertebrates 12", hosted by the Leibniz Institute for Zoo and Wildlife Research and held between 28th - 31st August, 2011 at the Schloss Friedrichsfelde and the Leibniz Institute for Zoo and Wildlife Research, Berlin, Germany. Chemical Signals in Vertebrates 12 contains the latest research on chemical communication relevant to vertebrates, particularly focusing on new research since the previous meeting in 2006. Topics covered include chemical ecology, biochemistry, behaviour and neurobiology of vertebrates. A broad range of taxonomic groups are discussed, including fish, amphibian, reptiles, birds and mammals including humans. Contributions address a range of topics including new directions in semiochemistry, predator avoidance, olfactory functions including recognition within species, sexual communication and social integration, maternal-offspring communication and applications for conservation. About the editors: Dr Marion L. East is a research scientist in the Department of Evolutionary Ecology at the Leibniz Institute for Zoo and Wildlife Research where she heads the Spotted Hyena Research Group. Dr Martin Dehnhard is a research scientist in the Department of Reproduction Biology where he heads the endocrine and the pheromone laboratory.